Denitration by oxidation-absorption with polypropylene hollow fiber membrane contactor. (15th November 2017) - Fang, Zhongqiu; Yu, Xiaochen; Tang, Weiqiang; Yu, Xinhai; Zhao, Shuangliang; Tu, Shan-Tung
Graphical abstract: Highlights: NO removal efficiency achieved 91.2% using PP membrane contactor and H2 O2 saline aqueous solution. Addition of NaCl to H2 O2 solution increases solubility of NO and therefore promotes NO removal. SO2 concentration decreased below 100 ppb which alleviated the burden of desulfuration. Abstract: Development of cost-efficient denitration technologies has been a challenging task in chemical industry. Here we proposed a new denitration method by using polypropylene hollow fiber membrane contactor, through which the NO gas from a simulative flue gas was absorbed into a saline aqueous solution, and then oxidized by the added H2 O2 . We demonstrated that the numerous pores in the semipermeable membrane and the addition of NaCl gave rise to a high-efficient oxidation-absorption process. By combining with a theoretical study upon both classical and quantum density functional theories, we extensively examined the effects of different operation parameters including the gas and liquid flow rates, the concentrations of H2 O2 and NaCl in the solution and SO2 in the mimic flue gas, the absorption temperature and the circulating time. The optimal operation parameters were identified. Finally, along with a designed industrial flow chart we evaluated the cost-efficiency of this proposed method, and found that this method could be more competitive than the current mainstream technologies for flue gas denitration.